ChemInform Abstract: Mn‐Catalyzed Highly Efficient Aerobic Oxidative Hydroxyazidation of Olefins: A Direct Approach to β‐Azido Alcohols. Issue 42 (October 2015) - Sun, Xiang; Li, Xinyao; Song, Song; Zhu, Yuchao; Liang, Yu‐Feng; Jiao, Ning
Abstract Azido radical generation employing air as the terminal oxidant is disclosed as the key process for this transformation.